Customer engagement in the co-creation of value: a look at financial institutions of Guayaquil - Cuadrado Gagñay, José Leonardo (2023)
In Ecuador, financial institutions are increasinglycompetitive and develop in a changing environment,which is why they need to set new challenges andpresent their clients with a portfolio of diversifiedproducts and services compared to other entities inthe sector. The objective of the investigation was todetermine the incidence that the client’s commitmenthas in the co-creation of value of financial services inthe banking institutions of Guayaquil. The researchapproach was quantitative and correlational in scope,characterized by being an exploratory and confirmatoryfactor analysis; the technique for data collection wasthe survey; The instrument used was the questionnairecarried out on the QuestionPro virtual platform.The population under study were the inhabitants ofGuayaquil who correspond to ages between 15 and 55years, in which a convenience sample of 395 peoplewas determined, with a confidence level of 95% andwith a margin of error of 5%. For the processing ofthe data, the SPSS software was used, in addition,Cronbach’s Alpha was applied to determine thereliability regarding the dimensions accompanied bytheir correlations, and LISREL to verify the feasibilityof the model and to verify the following hypothesis.The results of the investigation determined that theH1 hypothesis is approved, that is, that the client’scommitment does have a positive effect on the cocreationof value in financial services in the bankinginstitutions of Guayaquil. platform. The population under study was 60% of 2.654.433 inhabitants in the city of Guayaquil who correspond to ages between 15 and 55 years. In order to carry out an analysis with a greater degree of effectiveness, a convenience sample of 395 people was determined, with a confidence level of 95% and a margin of error of 5%. For the data processing, the SPSS software was used, applying Cronbach's Alpha to determine the reliability regarding the dimensions accompanied by their correlations, and LISREL to verify the feasibility of the model and to verify the following hypothesis. The results of the investigation determined that the H1 hypothesis is approved, that is, that the client's commitment does have a positive effect on the co-creation of value in financial services in the banking institutions of Guayaquil.